Fluorescence turn on amine detection in a cationic covalent organic framework - Das, Gobinda; Garai, Bikash; Prakasam, Thirumurugan; Benyettou, Farah; Varghese, Sabu; Sharma, Sudhir Kumar; Gándara, Felipe; Pasricha, Renu; Baias, Maria; Jagannathan, Ramesh; Saleh, Na’il; Elhabiri, Mourad; et al. (Nature communications, 2022)
Ionic covalent organic frameworks (iCOFs) are new examples of porous materials and have shown great potential for various applications. When functionalized with suitable emission sites, guest uptake via the ionic moieties of iCOFs can cause a significant change in luminescence, making them excellent candidates for chemosensors. In here, we present a luminescence sensor in the form of an ionic covalent organic framework (TGH + •PD) composed of guanidinium and phenanthroline moieties for the detection of ammonia and primary aliphatic amines. TGH + •PD exhibits strong emission enhancement in the presence of selective primary amines due to the suppression of intramolecular charge transfer (ICT) with an ultra-low detection limit of 1.2 × 10 ‒7 M for ammonia. The presence of ionic moieties makes TGH + •PD highly dispersible in water, while deprotonation of the guanidinium moiety by amines restricts its ICT process and signals their presence by enhanced fluorescence emission. The presence of ordered pore walls introduces size selectivity among analyte molecules, and the iCOF has been successfully used to monitor meat products that release biogenic amine vapors upon decomposition due to improper storage. Ionic covalent organic frameworks (iCOFs) are new examples of porous materials and show great potential for various applications. Here, the authors demonstrate functionalization of an iCOFs with suitable emission sites and application as chemosensor for amine detection with high sensitivity which can be used to monitor meat spoilage.